COMPARATIVE STEM ANATOMY OF EIGHT SELECTED WILD PLANT SPECIES FROM PAPILIONACEAE FAMILY IN WESTERN DESERT DISTRICT (DWD) - M. O. Mousa; I. M. Ayyed; S. S. Shahatha; N. M. Abood; F. H. Mukhlif; S. A. Alkubaisy; A. M. A. AL-Kasiy (مجلة الأنبار للعلوم الزراعية)
Eight selected wild plant species from the Papilionaceae family were collected and identified in the Western Desert District of Iraq. Which belongs to 5 genera, namely, the genus Astragalus L., represented by the species A. crispocarpus Nab., the genus Lotus L., represented by the species L. halophilus Boiss., and the genus Medicago L., which includes the species M. laciniata (L.) Mill. and M. minima (L.) Bratal. and M.rigidula (L.) All., the genus Ononis L. represented by the two species O. reclinta L. and O. sicula Guss., and the genus Trigonella L. represented by the species T. anguina Del., which were Identified in Anbar University Herbarium. Depending on the direct manual cutting method, the transverse section of the stem were prepared, and the samples were photographed and characteristics of the stem gave important differences that are very useful in isolating species taxonomically , the transverse sections varied between circular, tetrangular and polyangular-circular shapes, and the chlorenchyma tissue had a clear variation, as the number of its rows ranged between 1 row in M. laciniata to 4 rows in M. minima. The Sclerenchyma tissue, whose rows ranged from 4 to 14 rows, varies in species. The vascular bundles were characterized by the almost constant number in one species, which ranged from 9 to 14 vascular bundles. The vascular bundles and xylem arms in one bundle gave stable characteristics, and their numbers ranged between 2 arms in O. sicula to 8 arms in T. anguina.